Foliar and tuber late blight resistance in a Solanum tuberosum breeding population - Mayton, H.; Griffiths, H.; Simko, I.; Cheng, S.; Lorenzen, J.H.; Jong, W. de; Fry, W.E. (Wiley, 2010)
The purpose of this research was to identify the genetic basis of foliar and tuber resistance to Phytophthora infestans in a potato breeding population developed from a cross between two tetraploid Solanum tuberosum lines, NY121 and NY115. The parent with high foliar resistance, NY121, was highly susceptible to tuber blight. Foliar resistance was assessed in field trials, while tuber blight was assessed both in the field and in the laboratory. A quantitative trait locus (QTL) explaining ca. 50% of the phenotypic variance for foliar resistance was located on the lower arm of linkage group V, and was loosely associated with tuber blight resistance (significantly in one of two trials). This QTL was confirmed in a separate sample from the same population. Tuber blight detected via laboratory assays was not correlated with tuber blight incidence in the field. Most markers associated with tuber blight resistance were not associated with foliar resistance and most markers associated with foliar resistance were not associated with tuber blight resistance.